Definition of a Simplified Design Procedure of Seismic Isolation Systems for Bridges. Issue 3 (2nd July 2020) - Furinghetti, Marco; Pavese, Alberto
Abstract: In the recent past, numerical and experimental investigations on full-scale isolators have led to extensive improvements in seismic isolation techniques for bridge structures. Significant advances in dynamic testing techniques have been made at both software and hardware levels, and the response of an isolated bridge can be realistically simulated. In general, the response of an isolated bridge structure is strongly affected by the valley topography; therefore, high piers may not need isolation devices, since they are flexible enough to accommodate the design displacement in the elastic range. On the other hand, at those locations no hysteretic damping is provided and higher displacements can be achieved, compared to the maximum displacement allowance. In this work, a simplified procedure is proposed for the optimization of isolation systems for bridge structures. The seismic response of a designed case study structure is investigated through nonlinear time history analyses, and the effective contributions of both the nonlinear hysteretic behaviour of isolators and the elastic response of piers are considered. Regarding displacement and force responses in particular, the results show a very good agreement between mean and single-event peak responses, and the corresponding values returned by the proposed design procedure.